1988
DOI: 10.1055/s-2006-962411
|View full text |Cite
|
Sign up to set email alerts
|

Molluscicidal Saponins fromSesbania sesban

Abstract: The phytochemical investigation of the aerial parts of Sesbania sesban Merrill (Leguminosae) afforded three glucuronide derivatives of oleanolic acid. Among them, saponin 1, identified as 3-0-[a-L-rhamnopyranosyI-(1-*3)-3-D-glucuronopyranosyl]-oIeanolic acid, was responsible for the molluscicidal activity of the plant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 6 publications
0
21
0
Order By: Relevance
“…High saponin levels were observed in Telferia ocidentalis, Colocacia argente, Lunea taraxacifolia and Ammmarantus viridis, having saponin in mg/100g dry weight, well above 400. Such high level concentration of saponin may necessitate processing that might reduce level of saponin because of its ant-nutrients and other undesirous features such as increasing the permeability of the small intestine, growth impairment and decreased food conversion [19,20] and effect on fertility [21,22]. Thus, intake of these vegetables without proper processing may lead to saponin toxicity, for instance consumption of 100g of fresh Telferia occidentalis would expose the consumer to about 186mg of saponin.…”
Section: Discussionmentioning
confidence: 99%
“…High saponin levels were observed in Telferia ocidentalis, Colocacia argente, Lunea taraxacifolia and Ammmarantus viridis, having saponin in mg/100g dry weight, well above 400. Such high level concentration of saponin may necessitate processing that might reduce level of saponin because of its ant-nutrients and other undesirous features such as increasing the permeability of the small intestine, growth impairment and decreased food conversion [19,20] and effect on fertility [21,22]. Thus, intake of these vegetables without proper processing may lead to saponin toxicity, for instance consumption of 100g of fresh Telferia occidentalis would expose the consumer to about 186mg of saponin.…”
Section: Discussionmentioning
confidence: 99%
“…The phytochemical investigation of the aerial parts of Sesbania sesban Merrill (Fabaceae) afforded three glucuronide derivatives of oleanolic acid. Among them, the saponin considered to be responsible for the molluscicidal activity of the plant was identified as 3-O-[α-L-rhamnopyranosyl-(1→3)-β-D-glucuronopyranosyl oleanolic acid [65]. [66].…”
Section: Saponinsmentioning
confidence: 99%
“…The absolute configuration of 42 was determined from LC-NMR data of the Mosher ester derivative [38]. (65) respectively, the p-coumaroyl moiety of the latter existing in either the trans or cis configuration. In addition, harpagide, harpagoside, 8-O-trans-p-coumaroylharpagide, procumbide and verbascoside were isolated and identified [48].…”
mentioning
confidence: 99%
“…Efforts were then mounted to utilize this property of saponins to control diseases such as schistosomiasis. Saponins extracted from many other sources were also seen to have similar molluscicidal properties, for example purified Sesbania sesban saponins at 3-25 mg/kg (Dorsaz et al 1988) and purified saponin mixtures from Maesa lanceolata at above 5 parts per million (Sindambiwe et al 1998) have been found to be active against Biomphalaria glabrata. The molluscicidal activity of the saponins may be due to their characteristic detergent effect on the soft body membranes of the molluscs.…”
Section: Introductionmentioning
confidence: 99%